Violation of the Agreement Maxim Regarding the Existence of Police in the Comment Section of Bangsamahardika's Instagram Post - Maharani, Sasa (Southeast Asian Language and Literature Studies, 2025)
ABSTRACT This study aims to analyze the forms of impoliteness in the comment section of posts by the Instagram account Bangsamahardika, specifically focusing on violations of the agreement maxim based on Leech's politeness theory. The research adopts a descriptive qualitative approach, with data collected through digital observation of comments on five Instagram posts by Bangsamahardika during the period of December 1–10, 2024. The collected data were recorded and analyzed using pragmatic theory to understand the context and meaning of impolite comments. The findings reveal three main types of violations of the agreement maxim: identity, function, and actions of the police. First, the identity of the police, characterized by their brown uniforms, often becomes the target of criticism and satire, such as the term "brown party," reflecting public skepticism about the institution's neutrality. Second, the police's function as protectors, guardians, and enforcers of the law is questioned through comments indicating abuse of power and ethical violations. Third, police actions perceived as repressive or excessively violent lead to negative comments that damage the institution's image. These violations reflect a gap between the ideal role of the police and public expectations, exacerbated by ineffective communication, workplace cultures that fail to uphold integrity, and public distrust of the police institution. This study highlights the importance of understanding the agreement maxim to maintain polite communication on social media. As a recommendation, police institutions should enhance ethical education and professionalism, while the public is encouraged to provide more constructive criticism. Social media can also be utilized to build transparency and a positive image through active engagement between the police and the community. With these measures, it is expected that public trust in the police can be restored, and the quality of discussions on social media can improve. Keywords: impoliteness; agreement maxim; social media